Artificial Intelligence and Social Media on Academic Performance and Mental Wellbeing: Students' Perceptions of the Impact of the Era of Smart Learning - Andi Azzahfira Putri Suhaoping; Eunike Patricia (PT. Global Research Collaboration, 2025)
Background/Context: The integration of artificial intelligence (AI) and social media has significantly transformed how university students learn in the digital era. AI supports personalized learning, improves material comprehension, and enhances productivity, while social media facilitates academic collaboration. However, both also present challenges, such as decreased learning independence, social pressure, and mental health concerns.Objective/Purpose: This study aims to analyze the impact of AI and social media use on students’ academic performance and mental well-being.Method: A quantitative cross-sectional design was employed. Data were collected using a Likert-scale questionnaire completed by 91 active university students. Descriptive statistics (mean, median, mode, standard deviation) and correlational analysis using Pearson’s test, along with linear regression, were conducted with the support of Jamovi software.Results:The findings reveal that AI positively contributes to learning effectiveness, motivation, and personalized content, while also reducing academic stress. However, excessive use may lower students’ learning independence. Meanwhile, social media promotes academic and emotional interaction, but high-intensity use tends to increase anxiety, social pressure, and decreased concentration in learning.Conclusion:AI plays a strategic role in improving educational quality, whereas social media requires mindful management to prevent negative effects on students’ mental well-being. The study recommends digital literacy and time management strategies to maintain a healthy balance of technology use in higher education. well-being.